Pengaruh Kepemimpinan dan Motivasi terhadap Kinerja Karyawan UPT Bandar Udara Abdulrachman Saleh Malang - Khaerotunisa, Fika (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The purpose of this research is to find out whether leadership and motivation influences the performance of UPT Abdulrachman Saleh Airport Malang employees, whether leadership and motivation affect the performance of UPT Abdulrachman Saleh Airport Malang employees, and how much leadership and motivation influence together. on the performance of UPT Abdulrachman Saleh Airport Malang employees. This study uses a quantitative approach. The data source used in this study was obtained from distributing questionnaires to UPT Abdulrachman Saleh Airport Malang employees as many as 89 respondents. To determine the number of samples in this study, researchers used the Nonprobability Sampling technique with saturated sample techniques. The results of the study were concluded to answer the formulation of the problem, that: The leadership variable (X1) has an effect on the performance variable (Y), as evidenced by the t-count value that is greater than t-table, namely 2.859 > 1.987 and the significance value is smaller than the probability value, namely 0.005 < 0.05; The motivational variable (X2) has an effect on the performance variable (Y), as evidenced by the t count value that is greater than t table, namely 3.388 > 1.987 and the significance value is smaller than the probability value, namely 0.005 < 0.05; Variable X1 and variable X2 together have a significant effect on variable Y, as evidenced by the calculated f value that is greater than f table, namely 25.713 > 3.10 and the significance value is smaller than the probability value, namely 0.000 < 0.05; It is known that the R Square value is 0.374, meaning that leadership and motivation affect the performance of UPT Abdulrachman Saleh Airport Malang employees by 37.4%. Keywords: leadership, motivation, performance, malang abdulrachman saleh airport.